Collective Intentionality and Micro-macro Explanations - the Case of Routines - Makowski, Piotr Tomasz (Sensus Historiae, 2022)
The purpose of the article is to shed light on the nature of organizational routines, taking into account the research traditions of philosophy of action and analytical sociology. The article proposes a perspective that integrates different research disciplines and reveals the complexity of the issue of collective intentionality.